Night people - Condon, Chris (Comics writer) (Oni Press, 2025)
"A pair of murderous lovers in Florida carrying out a bloody agenda. A perverse political and religious power struggle between a brother and a sister. An easygoing drifter who suddenly finds himself a fugitive on the run. And a bright-eyed young girl discovering her place in the cold dark world. At the end of the twentieth century, chaos and horror were the American dream"--